The Influence of Sales Growth, ROE, and Size on Corporate Social Responsibility - Animah Animah; Elin Erlina Sasanti; Bambang Bambang (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2020)
Corporate Social Responsibility (CSR) is a series of corporate actions that appear to improve social products, expand the reach of the company beyond the explicit economic interests of the company, with the consideration that such actions are not required by law. This study aims to determine the effect of sales growth, Return on Equity, and Size on CSR. CSR in this study is measured by two approaches, namely CSR based on accrual basis (assumed CSR) and CSR based on cash basis (CSR fulfillment). This research wasconducted at companies listed on the Indonesia Stock Exchange in 2015-2017. The results showed that sales growth, Return on Equity and size did not affect the assumed CSR. However, the results of the study also showed that company size has influence on CSR fulfillment, while sales growth and ROE do not have an influence on CSR fulfillment.